Adsorption Technology for Water and Wastewater Treatments - Tran, Hai Nguyen (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The presence of pollutants (i.e., emerging contaminants, radionuclides, potential toxic metals, dyes, etc.) in water has a negative impact on the environment and presents a potential health risk for inhabitants. Among the existing technologies (i.e., advanced oxidation process, membrane filtration, biodegradation, etc.) that are used to remove them from water, adsorption has garnered significant interest due to its low cost and fast removal. The development of advanced materials and their application for water treatments have recently caught the attention of researchers.This reprint aimed to establish updated information on adsorption technology for water and wastewater treatments. The submissions selected for this SI focus on (1) applying reality technology for water and wastewater treatments and (2) exploring detailed adsorption mechanisms using current data (i.e., comparing changes in the properties of adsorbents before and after adsorption using appropriate techniques).